25. IMPACT OF CONTINUOUS TRAINING AT HANOI MEDICAL UNIVERSITY IN THE PERIOD 2015-2020: PERSPECTIVES OF STUDENTS AND EMPLOYERS (Vietnam Journal of Community Medicine, 2025)
Objective: This study describes the impact of a continuous training program at Hanoi Medical University.Methods: A cross-sectional study combining quantitative and qualitative approaches. A total of 152 alumni responded to a self-administered questionnaire, and in-depth interviews were conducted with 7 alumni and 14 unit leaders where the alumni worked. Kirkpatrick's training evaluation model was applied, focusing on behavioral changes in alumni after completing the course and returning to work.Results: After the course, 86.8% of alumni felt more confident and independent in performing their professional duties, and 80.3% participated in training or supporting colleagues with the knowledge they had acquired, receiving high professional evaluations from peers and patients. Over 70% of alumni implemented new techniques after the course, and 61.1% of alumni and colleagues applied 1-5 new techniques together. Alumni and leaders noted that alumni helped reduce the workload after graduation.Conclusion: CME programs have contributed to the professional development of healthcare staff and improved the operational effectiveness of their units.
Keywords: Continuous training; professional improvement; student perspectives